The missing slope: paradoxical shortening of activated partial thromboplastin time in a patient on unfractionated heparin therapy - Lapić, Ivana (Array, 2021)
This case report describes false shortening of activated partial thromboplastin time (aPTT) due to erroneous optical reading of the clotting point in the presence of unfractionated heparin (UFH), and a biphasic waveform. Activated partial thromboplastin time performed on a coagulometer with photo-optical detection yielded an ambiguous clotting curve characterized by an early and steady decrease in light transmittance throughout the whole measuring range, with the clotting point read at 65 seconds. Further investigations included measurement of aPTT by means of a mechanical clot detection method as well as determination of another heparin-sensitive coagulation assay, that is thrombin time (TT), both being unmeasurably prolonged (>150 seconds). Communication with clinicians revealed that the patient was on continuous UFH therapy and had an underlying sepsis, with highly elevated C-reactive protein (289 mg/L). The aPTT measurements requested at three timepoints later during the same day revealed gradual aPTT shortening and unveiled a peculiar biphasic waveform pattern. In this case, unmeasurably prolonged aPTT due to UFH therapy was masked by a biphasic aPTT curve pattern making only the first slope of the biphasic waveform visible within the measuring range. The early decrease in plasma light transmittance mimicked optical changes related to clot formation, thus causing erroneous optical reading and yielding a falsely shortened aPTT. This case emphasizes that such a pattern should be carefully inspected, especially when a combination of a critically ill condition and UFH therapy is present, in order to prevent erroneous reporting of aPTT and potential adverse effects on patient care.